Legal Liability of Notaries in Bad Credit Disputes through the Foreclosed Collateral Mechanism - Fadilah, Avisa Indah Nur (Proceedings of International Conference of Graduate School on Sustainability, 2026)
This study examines the legal responsibilities of Notaries in disputes arising from the settlement of non-performing loans (NPLs) through voluntary Foreclosed Collateral mechanisms within Rural Credit Banks (RCBs) in Indonesia. This article employs an empirical legal method by using qualitative data obtained through structured interviews with key practitioners, namely a senior executive in RCBs and a practicing Notary/Land Deed Official, to analyse the statutory framework and judicial reasoning in the civil and criminal disputes arising from the case of I Made Puja v. RCBs Saraswati Ekabumi in Denpasar District Court Verdict No. 512/Pdt.G/2021/PN Dps. The findings demonstrate that the ratification of voluntary collateral transfer deeds and subsequent sale and purchase deeds by a Notary plays a decisive role in judicial assessments of legal certainty, consensual intent, and the absence of coercion. The study finds that courts attribute substantial evidentiary value to authentic deeds prepared by Notaries, particularly in determining the voluntariness and legality of Foreclosed Collateral transactions, thereby undermining debtor claims of procedural irregularities. Although Notaries are formally required to maintain neutrality, their institutional position as public officials places them at the center of legitimizing creditor asset recovery processes conducted through voluntary foreclosure. The legal certainty generated by notarial acts effectively protects both financial institutions and Notaries from post-execution disputes, provided that the applicable procedural requirements are fulfilled. This study underscores the need for more straightforward regulatory guidelines to strengthen notarial impartiality in practice and ensure balanced legal protection for both creditors and debtors in voluntary foreclosure mechanisms.